Fungal-mediated synthesis of multimetallic nanoparticles: mechanisms, unique properties, and potential applications - Sidhu, Amanpreet K.; Agrawal, Sanskruthi B.; Verma, Naveen; Kaushal, Priya; Sharma, Madhvi (Frontiers in Nanotechnology, 2025)
Multimetallic nanoparticles (MMNPs) produced by fungus-mediated synthesis have attracted a lot of interest as an environmentally friendly and sustainable nanotechnology method. Fungi are effective bio-factories that create complex nanoparticles with special qualities by using their metabolic and enzymatic capabilities. When compared to their monometallic counterparts, MMNPs—which are composed of combinations of two or more metals—offer synergistic benefits such increased catalytic activity, higher stability, and superior biocompatibility. In addition to highlighting the structural diversity of MMNPs, such as core-shell, alloy, and Janus configurations, this review investigates the mechanisms underpinning fungal-mediated synthesis, including enzymatic reduction and stabilisation pathways. Additionally covered are characterisation methods for examining functionality, morphology, and composition. The potential applications of MMNPs synthesized by fungi in biomedicine, environmental remediation, biosensing, and catalysis are highlighted in the article. This green synthesis method, which makes use of the natural benefits of fungus and multimetallic systems, responds to the increasing need for sustainable nanomaterials and opens the door to novel uses in both the scientific and industrial fields.